ACTIVE LIVING GEARY COUNTY - Farley, Richelle (My University, 2016)
Many adults are not meeting the physical activity guidelines of 150 minutes per week. Only about 20 percent of U.S adults or one in five adults are meeting both the aerobic and muscle strengthening components of the physical activity recommendations (CDC). This inactivity also correlates with the increasing obesity rates where two in three adults are considered overweight or obese (NHANES, 2009-2010). Many programs have been developed to address this issue in children and youth through after school programs and national campaigns such as “Let’s Move”. However, there are specific populations that need to be targeted as their environment changes through the course of their lives. Many approaches have been made to target adults whether it be through the workplace, school, internet or community-based. These approaches include behavioral change strategies such as goal setting, social support, self-reward, and problem solving. Programs based on these health behavior strategies have strong evidence of their effectiveness in increasing physical activity among adults (Task Force on Preventative Services, 2002). According to the health assessment conducted in 2014, 25.9% of Geary county residents reported doing enough physical activity to meet both the aerobic (i.e. 150 minutes of moderate-intensity aerobic activity per week such as brisk walking) and strengthening exercise (i.e. activities on 2 or more days/week that work major muscle groups) recommendations. However, the Geary County Health assessment also highlighted that there are few environments that support physical activity. The Geary County Health Department has recognized the need to promote a more physically active community in conjunction with its mission to improve the public health and the well-being of Geary County residents. This report covers projects, activities and learning objectives conducted during a field experience for fulfillment of a Master in Public Health at Kansas State University. The main project was to provide a physical activity program for residents where they can learn ways to incorporate physical activity into their daily routines. This program was one of the first step for the Health department in its mission to tackle the fourth leading cause of death which is physical inactivity (WHO, 2010).
Keywords: Geary County Kansas; Physical activity; Public health